The book of lost saints - Older, Daniel José (Imprint, 2019)
"The spirit of Marisol, who vanished during the Cuban Revolution, visits her nephew, Ramon, in modern-day New Jersey, and her presence prompts him to investigate the story of his ancestor, unaware of the forces driving him on his search"--